2015
DOI: 10.1242/jcs.162651
|View full text |Cite
|
Sign up to set email alerts
|

The small GTPase Arl8b regulates assembly of the mammalian HOPS complex to lysosomes

Abstract: The homotypic fusion and protein sorting (HOPS) complex is a multi-subunit complex conserved from yeast to mammals that regulates late endosome and lysosome fusion. However, little is known about how the HOPS complex is recruited to lysosomes in mammalian cells. Here, we report that the small GTPase Arl8b, but not Rab7 (also known as RAB7A), is essential for membrane localization of the human (h)Vps41 subunit of the HOPS complex. Assembly of the core HOPS subunits to Arl8b- and hVps41-positive lysosomes is gui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
157
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 127 publications
(167 citation statements)
references
References 64 publications
8
157
0
Order By: Relevance
“…In addition to showing that these processes clearly differ mechanistically, this fits well with the predominantly lysosomal localization of Drosophila Gie/Arl8 and its mammalian orthologs [25,71]. …”
Section: Discussionsupporting
confidence: 72%
See 3 more Smart Citations
“…In addition to showing that these processes clearly differ mechanistically, this fits well with the predominantly lysosomal localization of Drosophila Gie/Arl8 and its mammalian orthologs [25,71]. …”
Section: Discussionsupporting
confidence: 72%
“…The small GTPase ARL8B is required for LE-lysosome fusion as the lysosomal HOPS receptor in mammals [25]. Gie/Arl8, the single Drosophila ortholog for mammalian ARL8A/B, also localizes to lysosomes [71], but a phenotypic description of Gie/Arl8 loss-of-function in flies is lacking.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent data has suggested that in metazoan cells, Arl8b directly binds to Vps41 and regulates assembly of the HOPS complex on lysosomal membranes. 23,25,46,47 Accordingly, Arl8b-depletion impaired lysosomal localization of Vps41 and other HOPS subunits. Furthermore, Arl8b-binding was required for Vps41 function in epidermal growth factor receptor (EGFR) trafficking to lysosomes and its lysosomal degradation.…”
Section: Arl8b Regulates Lysosomal Motility Through Interaction Withmentioning
confidence: 97%